Uji Aktivitas Antiglikemik In Vitro Ekstrak Etanol Daun Karamunting (Melastoma malabathricum L.) Dengan Metode Sokletasi - Afra, Fairuz Yaumil; Muthia, Rahmi; Fauzana, Erwin; Nurmansyah, Dian; Normilawati, Santi (Universitas Borneo Lestari, 2024)
health problem, especially due to population growth, aging, poor lifestyle and diet, and high morbidity rates indicated by the increasing number of deaths each year. This study was conducted with the aim of determined the antidiabetic activity of samples used the Nelson-Somogi method. Samples were soxhleted used 96% ethanol solvent. The results of phytochemical screening, the extract showed positive content of phenol, flavonoid, saponin, tannin and steroid compounds. The in vitro glucose level reduction test used a UV-Vis spectrophotometer. The wavelength used was 740 nm and the incubation time was 25 minutes. The percentage of sugar level reduction after added the extract at a concentration of 1, 2 3; 4; 5 ppm was 28.56%; 40.48 percent; 51.99%; 60.74%; 70.72 percent. The linear regression equation obtained y = 10.458x + 19.128 R2 value = 0.9964. It can be concluded that the 96% ethanol extract of the sample has the potential to reduce blood sugar levels with an EC50 value of 2.95 ppm.